Exercise reduces intramuscular stress and counteracts muscle weakness in mice with breast cancer. Issue 2 (15th February 2022) - Mader, Theresa; Chaillou, Thomas; Alves, Estela Santos; Jude, Baptiste; Cheng, Arthur J.; Kenne, Ellinor; Mijwel, Sara; Kurzejamska, Ewa; Vincent, Clara Theresa; Rundqvist, Helene; Lanner, Johanna T.
Abstract: Background: Patients with breast cancer exhibit muscle weakness, which is associated with increased mortality risk and reduced quality of life. Muscle weakness is experienced even in the absence of loss of muscle mass in breast cancer patients, indicating intrinsic muscle dysfunction. Physical activity is correlated with reduced cancer mortality and disease recurrence. However, the molecular processes underlying breast cancer‐induced muscle weakness and the beneficial effect of exercise are largely unknown. Methods: Eight‐week‐old breast cancer (MMTV‐PyMT, PyMT) and control (WT) mice had access to active or inactive in‐cage voluntary running wheels for 4 weeks. Mice were also subjected to a treadmill test. Muscle force was measured ex vivo . Tumour markers were determined with immunohistochemistry. Mitochondrial biogenesis and function were assessed with transcriptional analyses of PGC‐1α, the electron transport chain (ETC) and antioxidants superoxide dismutase (Sod) and catalase (Cat), combined with activity measurements of SOD, citrate synthase (CS) and β‐hydroxyacyl‐CoA‐dehydrogenase (βHAD). Serum and intramuscular stress levels were evaluated by enzymatic assays, immunoblotting, and transcriptional analyses of, for example, tumour necrosis factor‐α (TNF‐α) and p38 mitogen‐activated protein kinase (MAPK) signalling. Results: PyMT mice endured shorter time and distance during the treadmill test (~30%, P  < 0.05) and ex vivo force measurements revealed ~25% weaker slow‐twitch soleus muscle ( P  < 0.001). This was independent of cancer‐induced alteration of muscle size or fibre type. Inflammatory stressors in serum and muscle, including TNF‐α and p38 MAPK, were higher in PyMT than in WT mice ( P  < 0.05). Cancer‐induced decreases in ETC ( P  < 0.05, P  < 0.01) and antioxidant gene expression were observed ( P  < 0.05). The exercise intervention counteracted the cancer‐induced muscle weakness and was accompanied by a less aggressive, differentiated tumour phenotype, determined by increased CK8 and reduced CK14 expression ( P  < 0.05). In PyMT mice, the exercise intervention led to higher CS activity ( P  = 0.23), enhanced β‐HAD and SOD activities ( P  < 0.05), and reduced levels of intramuscular stressors together with a normalization of the expression signature of TNFα‐targets and ETC genes ( P  < 0.05, P  < 0.01). At the same time, the exercise‐induced PGC‐1α expression, and CS and β‐HAD activity was blunted in muscle from the PyMT mice as compared with WT mice, indicative that breast cancer interfere with transcriptional programming of mitochondria and that the molecular adaptation to exercise differs between healthy mice and those afflicted by disease. Conclusions: Four‐week voluntary wheel running counteracted muscle weakness in PyMT mice which was accompanied by reduced intrinsic stress and improved mitochondrial and antioxidant profiles and activities that aligned with muscles of healthy mice.